2021
DOI: 10.1093/heapol/czab098
|View full text |Cite
|
Sign up to set email alerts
|

Presence of birth companion—a deterrent to disrespectful behaviours towards women during delivery: an exploratory mixed-method study in 18 public hospitals of India

Abstract: Birthing women require support, particularly emotional support, during the process of labour and delivery. Traditionally, across cultures, this support was made available by the continuous presence of a companion during labour, childbirth and the immediate post-partum period. However, this practice is not universal, especially in health facilities in low- and middle-income countries. This cross-sectional study was conducted in 18 tertiary health care facilities of India using a mixed-method approach. The quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This may be especially important in pandemic times, where the presence of lay companions has been limited, though their presence may be needed more than ever when there is shortage of staff (Kathuria et al 2020). This is a simple cost-effective way of providing beneficial support in all birth settings, promoting respectful maternity care (Singh et al 2021) and, by that, preventing future psychopathology sequela.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…This may be especially important in pandemic times, where the presence of lay companions has been limited, though their presence may be needed more than ever when there is shortage of staff (Kathuria et al 2020). This is a simple cost-effective way of providing beneficial support in all birth settings, promoting respectful maternity care (Singh et al 2021) and, by that, preventing future psychopathology sequela.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…Birth companions also reduce women's chances of being mistreated. Singh et al's [41] quantitative study in India revealed that women with birth companions were less likely to experience obstetric violence. From these bases, it is apparent that there is a need for concrete measures to facilitate accompanied delivery in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…They found that despite awareness of the importance and advantages of birth companions, it was the absence of defined hospital policies, lack of space, lack of privacy, and crowding in labor rooms that were reported as reasons birth companions were not allowed. They also reported that the presence of birth companions was negatively associated with incidences of disrespect and abuse of women [ 6 ]. Childbirth is a very personal event in a woman’s life, and the experiences (positive or negative) stay with her for a very long time.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO recommends that all women should have access to a birth companion of their choice [ 2 ]. Birth companions are commonly allowed in private maternity facilities in the country; however, very few government setups in India allow birth companions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%